PREPARATION AND IN-VITRO EVALUATION OF MICROBALLOON DRUG DELIVERY SYSTEM OF TELMISARTAN (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
In present study an attempt was made to prepare hollow microspheres (microballoons) of Telmisartan by emulsion solvent diffusion technique for sustained delivery by using polymers like Hydroxy Propyl Methyl Cellulose (HPMC) and Eudragit RS 100 in order to extend the drug release for about 12 h in the upper GIT, which may result in enhanced absorption and there by improved bioavailability. The particle size was determined by optical micrometer and average particle size was found to be in range of189.5± 2.63 to 124.33± 2.14. Formulation F7 containing HPMC and Eudragit polymer blend showed the best floating ability (91.26%) as compared with other formulations. From Scanning Electron Microscopy (SEM) it was observed that, microballoons were found to be spherical in shape with smooth surface texture with a hollow space within. Among all formulations, F7 showed appropriate balance between buoyancy and drug release rate of 98.32% in 12 h, which is considered as the best formulation.